Common Pokeweed - Brent Sellers; Jason Ferrell; Curtis Rainbolt (EDIS)
SS-AGR-123, a 2-page illustrated fact sheet by Brent Sellers, Jason Ferrell, and Curtis Rainbolt, provides key information on the biology, toxicity, cultural uses, and control of common pokeweed (Phytolacca americana) -- also called poke berry, pigeon berry, inkberry coakum, pocan bush, scoke, poke salad, and American nightshade. Published by the UF Department of Agronomy, May 2006. Reviewed November 2006.